UPAYA MENINGKATKAN KETERAMPILAN MENULIS SISWA MELALUI PERMAINAN KEMBANG KATA - Mayasari, Dian; Nurteti, Lilis; Azis, Abdul (Bestari, 2019)
This research is motivated by the learning experience of students who have entered kindergarten, and who have absolutely no learning experience entering kindergarten. Constraints there are still students who are not yet proficient in writing using appropriate punctuation, researchers choose the use of cognitive approaches through word development. The objectives of this study are: 1) To improve the performance of educators in preparing the Learning Implementation Plan (RPP) on Indonesian subjects using a cognitive approach through word development games in grade 3 MI 2 Cisaga; 2) To improve the ability of educators in implementing the learning process in Indonesian subjects by using a cognitive approach through word development games in MI 2 Cisaga; 3) To improve students' writing skills in Indonesian subjects at MI 2 Cisaga. The method used is the Kurt Lewin model of classroom action research (CAR). While the data collection techniques used are observation techniques, test techniques and descriptive analysis. After conducting research in MI 2 Cisaga, the researchers reached the following conclusions: 1) Educators have increased ability to compile lesson plans using cognitive approaches through word games, cycle I 90.05, cycle II 90.63 and cycle III 92.15; 2) Educators have increased the ability to carry out learning by using a cognitive approach through word play, cycle I 90.3, cycle II 90.4 and cycle III 91.7; 3) Students' writing skills using a cognitive approach through word development have increased, namely pre cycle 65.8, cycle I 70.6, cycle II 76 and cycle III 85.5. Thus, the use of cognitive approaches through word games can improve students' writing skills.